2016
DOI: 10.3892/mmr.2016.5786
|View full text |Cite|
|
Sign up to set email alerts
|

Glycogen synthase kinase-3β is required for epithelial-mesenchymal transition and barrier dysfunction in mouse podocytes under high glucose conditions

Abstract: Epithelial-mesenchymal transition (EMT) is important for diabetic nephropathy (DN). Podocytes are specialized epithelial cells, which form a major component of the glomerular filtration barrier. Podocyte damage has been suggested to be the primary mechanism behind the albuminuria associated with DN. The present study aimed to determine the function of glycogen synthase kinase (GSK)-3β in EMT and barrier dysfunction of mouse podocytes exposed to high glucose (HG) conditions. Matured and differentiated podocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This is congruous with another in vitro study, where GSK3b was found to mediate podocyte dedifferentiation and injury after exposure to high glucose medium. 47 On the contrary, Mariappan et al 48 claimed that the activation of GSK3b instead ameliorates diabetes-induced kidney injury. In their study, streptozotocininduced diabetic mice were treated with sodium nitroprusside, a nitric oxide donor that is able to activate GSK3b.…”
Section: Discussionmentioning
confidence: 99%
“…This is congruous with another in vitro study, where GSK3b was found to mediate podocyte dedifferentiation and injury after exposure to high glucose medium. 47 On the contrary, Mariappan et al 48 claimed that the activation of GSK3b instead ameliorates diabetes-induced kidney injury. In their study, streptozotocininduced diabetic mice were treated with sodium nitroprusside, a nitric oxide donor that is able to activate GSK3b.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in 2016 proved the function of GSK-3β both in podocyte dysfunction and EMT, which emphasized the hallmarks podocytes lost when undergoing EMT. 20 …”
Section: The Specialization Of Podocytementioning
confidence: 99%
“…Nedd4-2 is a member of the E3 ubiquitin ligase that mediates substrate protein ubiquitination mediated degradation by transferring ubiquitin from its homologous to the E6-AP carboxyl terminus (HECT) domain to substrate proteins ( Abriel and Staub, 2005 ; Rotin and Kumar, 2009 ). GSK3β participates in podocyte damage by affecting podocyte actin skeleton destruction and short foot mutations ( Xu et al, 2014 ; Guo et al, 2016 ; Li et al, 2016 ). Previous reports have demonstrated that GSK3β regulates the nuclear transcription of nephrin through the transcriptional repressor Snail ( Matsui et al, 2007 ; Wan et al, 2016 ; Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%